Diplomasi Maritim Indonesia di Tengah Ketegangan Regional - Risahdi, Muhammad; Lestari, Amin; Yulianto, Bayu Asih; Prakoso, Lukman Yudho; Legowo, Endro (Jurnal sosial dan sains, 2025)
This study examines Indonesia’s maritime diplomacy amid regional tensions in Southeast Asia. The research focuses on strategies employed to safeguard maritime sovereignty, strengthen regional cooperation, and mitigate potential conflicts in strategic waters such as the North Natuna Sea and the South China Sea. Utilizing a qualitative approach through document analysis, official reports, and expert interviews, the findings indicate that Indonesia’s maritime diplomacy effectively fosters intergovernmental coordination, enhances maritime surveillance, and strengthens Indonesia’s bargaining position in regional negotiations.